Recycled Low Density Poly Ethylene Plastic Powder Substitute for Sand in Mortar and Concrete - T, Gopikrishnan; Gautam Kumar; Mahendra Kumar; Rajdhar Dwivedi; Jitendra Sharma (International Journal of Sustainable Construction Engineering and Technology, 2025)
The mortar and concrete are essential materials for construction. The mortar and concrete are made from raw materials of cement, sand, aggregates and water. The sand is mined from riverbeds which results in environmental impacts. The environmental impacts can be reduced by substituting a low-cost replacement material for sand. The low-cost material used in this study is Recycled Low Density Poly Ethylene (R-LDPE) plastic powder. The R-LDPE is replaced in mortar and concrete mixes from 5% to 30%. The conjecture of this study is that the R-LDPE possessing excellent water repellent property will make the mortar and concrete less pervious to water. In this study, the selected mortar mix for testing is 1:3 and concrete mix for testing is M-45. The tests of compression, flexure, conventional seepage and Rapid Chloride Permeability Test (RCPT) is carried out. The suitable R-LDPE replacement percentage to the volume of the sand is identified as 15% for compression, flexure, conventional seepage and RCPT. The conjecture of this study fails as R-LDPE particles makes the mortar and concrete samples porous. The 15% R-LDPE replaced mortar and concrete to the volume of sand results is suitable for making porous concrete.